CD20‐Specific Immunoligands Engaging NKG2D Enhance γδ T Cell‐Mediated Lysis of Lymphoma Cells. (27th September 2017) - Peipp, M.; Wesch, D.; Oberg, H.‐H.; Lutz, S.; Muskulus, A.; van de Winkel, J. G. J.; Parren, P. W. H. I.; Burger, R.; Humpe, A.; Kabelitz, D.; Gramatzki, M.; Kellner, C.
Abstract: Human γδ T cells are innate‐like T cells which are able to kill a broad range of tumour cells and thus may have potential for cancer immunotherapy. The activating receptor natural killer group 2 member D (NKG2D) plays a key role in regulating immune responses driven by γδ T cells. Here, we explored whether recombinant immunoligands consisting of a CD20 single‐chain fragment variable (scFv) linked to a NKG2D ligand, either MHC class I chain‐related protein A (MICA) or UL16 binding protein 2 (ULBP2), could be employed to engage γδ T cells for tumour cell killing. The two immunoligands, designated MICA:7D8 and ULBP2:7D8, respectively, enhanced cytotoxicity of ex vivo ‐expanded γδ T cells against CD20‐positive lymphoma cells. Both Vδ1 and Vδ2 γδ T cells were triggered by MICA:7D8 or ULBP2:7D8. Killing of CD20‐negative tumour cells was not induced by the immunoligands, indicating their antigen specificity. MICA:7D8 and ULBP2:7D8 acted in a dose‐dependent manner and induced cytotoxicity at nanomolar concentrations. Importantly, chronic lymphocytic leukaemia (CLL) cells isolated from patients were sensitized by the two immunoligands for γδ T cell cytotoxicity. In a combination approach, the immunoligands were combined with bromohydrin pyrophosphate (BrHPP), an agonist for Vδ2 γδ T cells, which further enhanced the efficacy in target cell killing. Thus, employing tumour‐directed recombinant immunoligands which engage NKG2D may represent an attractive strategy to enhance antitumour cytotoxicity of γδ T cells.